Between-Limb Symmetry in ACL and Tibiofemoral Contact Forces in Athletes After ACL Reconstruction and Clearance for Return to Sport. Issue 4 (8th April 2022) - Kotsifaki, Argyro; Van Rossom, Sam; Whiteley, Rod; Korakakis, Vasileios; Bahr, Roald; D'Hooghe, Pieter; Papakostas, Emmanuel; Sideris, Vasileios; Farooq, Abdulaziz; Jonkers, Ilse
Background: Current return-to-sport (RTS) criteria after anterior cruciate ligament (ACL) reconstruction (ACLR) include demonstrating symmetry in functional and strength tests. It remains unknown if at the time that athletes are cleared to RTS, they exhibit between-limb symmetry in ACL and tibiofemoral contact forces or if these forces are comparable with those in uninjured athletes. Purposes: To (1) examine ACL and tibiofemoral contact forces in athletes who underwent ACLR and were cleared to RTS and (2) compare the involved leg to the healthy contralateral leg and healthy controls during functional tasks. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 26 male athletes who underwent ACLR were tested at the time of RTS during tasks that included single-leg vertical, horizontal, and side jumps; cutting maneuvers; and high-intensity running. We used an electromyography-constrained musculoskeletal modeling workflow to estimate ACL and tibiofemoral contact forces and compared the results with those of 23 healthy male participants. Results: The ACLR group presented no differences in peak tibiofemoral contact forces in the involved limb compared with the control group. However, there were significant between-limb differences mainly due to higher contact forces in the uninvolved (healthy) limb of the ACLR group compared with the control group. In the ACLR group, ACL forces were significantly higher in the uninvolved limb compared with the involved limb during cutting and running. Lateral contact forces were lower in the involved compared with the uninvolved limb, with large effect sizes during cutting ( d = 1.14; P < .001) and running ( d = 1.10; P < .001). Conclusion: Current discharge criteria for clearance to RTS after ACLR did not ensure the restoration of symmetric loading in our cohort of male athletes. ACL force asymmetry was observed during cutting and running, in addition to knee loading asymmetries on several tasks tested.